Pengaruh Model Pembelajaran Student Fasilitator and Expalning untuk Meningkatkan Hasil Belajar Siswa - Azisah Azisah; Basri Basri; Hamka Hamka (Journal on Education, 2025)
This research aims to determine the effect of the student facilitator and explain learning model to improve student learning outcomes at MTs Annurain Lonrae. The type of research used is experimental research with a quantitative approach. The data processed is a pre-test and post-test given to all class VIII.A students at MTs Annurain Lonrae. The data collection method in this research is the Test Instrument. The data processed using Instrument Tests are in the form of Validity Tests, Reliability Tests, Question Difficulty Level Tests and Question Discrimination Power Tests, and to answer the research hypothesis, Descriptive Statistics Tests and Infrential Statistics Tests are carried out. Based on the research results and existing data, researchers can conclude that the Student Facilitator and Explanig learning model has a positive influence on the learning outcomes of class VIII.A MTs Annurain Lonrae students. This can be proven from the results of the hypothesis test that has been carried out, obtained t count or 21.657 > 2.10982, so Ho is rejected and H1 is accepted.